Barriers and enablers of the idea generation process within a technically minded team: a case study of MCL Industries. - Sitkowska, F. (2016)
This dissertation is a consultancy project for MCL Industries which is a British SME operating in a B2B market. They are manufacturing and supplying industrial composites for the utility, technology and infrastructure markets. The aim of the dissertation is to identify barriers and enablers to the innovation process within the R&D team. The aim is achieved via a case study research investigating employees’ experiences of day-to-day work environment. First step of the research is a revision of academic knowledge about the idea generation, creativity and the relationship between organisational management and creativity. Next, the practical research is conducted using participant observation and semi-structured interviews. According to the findings R&D team’s innovatory behaviour is hindered by a lack of structure within the company and the team itself, poor communication, stress on resources and lack of organisational support. Also, the study shows that MCL Industries isn’t using any ideation techniques that could significantly improve the quality of the generated ideas. The study concludes with recommendations that address MCL’s problem with innovation.